The research productivity of new Brazilian PhDs in management: A few "star" performers outshine a mass of low performers. (20th June 2016) - Falaster, Christian; Ferreira, Manuel Portugal; Serra, Fernando Ribeiro
Abstract : Purpose: Doctoral programs are primarily intended to train new professors and researchers to take positions requiring research competency. This paper aims to observe the scientific production of 734 Brazilian new PhDs in management and the possible link between the scientific output of the graduates and doctoral program rank. Design/methodology/approach: Methodologically, the authors built a database collecting the journal publications of the first six years after doctoral degree of all PhDs in management graduated by Brazilian doctoral programs during the period of 1998-2008. The authors use cluster and descriptive analysis to explore PhD publication. Findings: Results show a great disparity of productivity, where 10 per cent of all new PhDs account for most of the Brazilian research productivity, while most of the PhDs have a very low performance – and that the CAPES (the Brazilian institutional system) qualification of doctoral programs is not a good predictor of the performance of the future graduates. Results are discussed to understand this productivity gap among researchers in a context of a developing country where support institutions are working to improve quantity and quality of publication. Practical implications: The results are useful for recruiters that need to decide between hiring new PhDs with low productivity graduated from high-ranked programs or new PhDs with high productivity from programs with more modest ranking. At least in part, the authors' results question the real impact that the doctoral program's prestige has on the performance of its graduates. Social implications: There are implications for the future candidates to a management PhD program, for the Directors of these programs and for the institutional agencies that regulate and promote science and that establish the prevailing rules and norms that researchers and institutions follow. Originality/value: The results are adamant in pointing out that there is a small group of highly productive new PhDs – that the authors called "stars". Generally speaking, they may find these "star" new PhDs in several doctoral programs. They have also found that some of the new PhDs have a relatively higher level of international papers published, but not necessarily a larger volume of publications. Meanwhile, most PhDs present a very low level of performance. This has important contributions to the way they perceive the doctoral education in management, especially in Ibero-America, revealing insights about the quality of PhDs and PhD courses.